Plasma Generation Atmospheric Pressure By Using Microwave Radiation - Ali, Farith Aqmal (2020)
Generating plasma at atmospheric pressure will have a significant impact on its application since it reduces energy consumption, costs as well as tackling the need of low-pressure space. This paper examines the suitable length and the best type of electrode to generate plasma as well as the impact of catalytic plate towards plasma formation. Through detailed investigation into the length of the electrode used which are 3 cm, 6 cm and 9 cm, it is confirmed that the half wavelength ratio which is 6 cm would be the ideal length for plasma generation. The type of electrode to generate a plasma would be related to the thermal conductivity value. With higher thermal conductivity, plasma generation at the tip of electrodes will be faster. For 55% (385 W) power setting, the longest time taken was 19.45 s by lead electrode and the shortest time was 6.75 s by aluminium electrode. For 77% (539 W), the maximum time was 8.4 s by lead electrode and the minimum time was 2.91 s by copper electrode. For 100% (700 W), the highest time was 5.91 s by lead electrode and the lowest time wis'2.77 s by iron electrode. After the research was done, the generation of plasma would be best if the catalytic plate is wrapped with copper metal sheet and bring closer to the tip of electrode. For plate without copper sheet, under 55% (385 W) power setting, the maximum time taken was 9.59 s with the height of 1.5 cm and the minimum time was 2.96 s with the height of 0.5 cm whereas for plate with copper sheet gave the maximum time of 4.13 s under 1.5 cm height and the minimum time of 3.49 s under the height of 0.5 cm. For plate without copper sheet under 77% (539 W) power setting, the maximum time taken was 8.51 s with the height of 1.5 cm and the minimum time was 2.95 s with the height of 0.5 cm whereas for plate with copper sheet gave the maximum time of 2.95 s under 1.5 cm height and the minimum time of 2.44 s under the height of 0.5 cm. For plate without copper sheet under 100% (700 W) power setting, the maximum time taken was 7.03 s with the height of 1.5 cm and the minimum time was 2.45 s with the height of 0.5 cm whereas for plate with copper sheet gave the maximum time of 2.85 s under 1.5 cm height and the minimum time of 2.15 s under the height of 0.5 cm. When the height is being reduced, the plasma generation will be faster due to more confined reaction zone.